Judges and argumentation - Figueroa Gutarra, Edwin (2012)
The construction of legal arguments by a judge requires the correlation of necessary concepts that identify the theory of law, the philosophy of law, the fundamental rights and the proposal of schools of legal argumentation. Our study offers a few initial thoughts on how the judicial work can be strengthened by identifying core concepts related to the proposed ideas and by providing arguments to justify them